2022
DOI: 10.5194/essd-14-3249-2022
|View full text |Cite
|
Sign up to set email alerts
|

EMO-5: a high-resolution multi-variable gridded meteorological dataset for Europe

Abstract: Abstract. In this paper we present EMO-5 (“European Meteorological Observations”, spatial resolution of 5 km), a European high-resolution, (sub-)daily, multi-variable meteorological dataset built on historical and real-time observations obtained by integrating data from 18 964 ground weather stations, four high-resolution regional observational grids (i.e. CombiPrecip, ZAMG – INCA, EURO4M-APGD, and CarpatClim), and one global reanalysis (ERA-Interim/Land). EMO-5 includes the following at daily resolution: tota… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Model 3 considers regional climatological factors while Model 4 addresses the potential climatological variations that may manifest at the level of individual stations. To that end, we use a higher resolution environmental data set, for both the daily temperature and the daily rainfall, from the Joint Research Centre Data Catalog—EMO (Thiemig et al., 2022). This data set is characterized by an enhanced spatial resolution of 1.5 km × 1.5 km.…”
Section: Velocity Variationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Model 3 considers regional climatological factors while Model 4 addresses the potential climatological variations that may manifest at the level of individual stations. To that end, we use a higher resolution environmental data set, for both the daily temperature and the daily rainfall, from the Joint Research Centre Data Catalog—EMO (Thiemig et al., 2022). This data set is characterized by an enhanced spatial resolution of 1.5 km × 1.5 km.…”
Section: Velocity Variationsmentioning
confidence: 99%
“…The rain and the temperature data were obtained from the NASA Langley Research Center (LaRC) POWER Project funded through the NASA Earth Science/Applied Science Program (https://power.larc.nasa.gov/) (Stackhouse, 2021) and from a Joint Research Centre Data Catalog—EMO (Thiemig et al., 2022). The seismic data are available at Instituto Nazionale di Geofisica e Vulcanologia (http://iside.rm.ingv.it/instruments) (INGV, 2005).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…For EWS driven by physically based models, hydrological simulations based on the same hydrological model configurations are generally preferred over in‐situ hydrological observations to define the initial conditions (especially as many of the state variables of hydrological models do not have observations) to ensure consistency in the modelling chain, regardless of the overall forecasting techniques (e.g., based on statistics, climatology or NWP information; Troin et al, 2021). For large‐scale distributed EWS requiring spatially consistent and continuous information, the hydrological reanalysis can be forced with atmospheric reanalysis (e.g., ERA5T; Hersbach et al, 2020 used in GloFAS), hybrid datasets (e.g., HydroGDF; Berg et al, 2021) or observation‐based datasets (e.g., EMO5 but updated in real‐time used in the CEMS European Flood Awareness System EFAS (Thiemig et al, 2022), or UK Met Office precipitation and potential evaporation used in UK Hydrological Outlook (Prudhomme et al, 2017)).…”
Section: Examples Of Applications Of Global Hydrological Reanalysismentioning
confidence: 99%
“…The dataset also showed that the river discharge reached record low levels across July and August in the Rhine river basin, just 1 year after record floods on the Rhine in July 2021, causing devastating impacts in public water supply, agriculture, power generation and industry or ecosystem. Whilst for Europe, studies such as that presented in Figure 7b do not necessarily rely on modelled weather reanalysis input thanks to a very dense meteorological observational network (Figure 7b uses the EMO5 dataset (Thiemig et al, 2022) as forcing data), similar rapid assessments are possible globally at any time using datasets such as C3S ERA5T and CEMS GloFAST.…”
Section: Examples Of Applications Of Global Hydrological Reanalysismentioning
confidence: 99%
See 1 more Smart Citation